HUKUM ADMINISTRASI NEGARA DAN IMPLEMENTASI ASAS-ASAS UMUM PEMERINTAHAN YANG BAIK DALAM SISTEM PEMERINTAHAN INDONESIA - Nilasari, Vivi; Frinaldi, Aldri; Roberia, Roberia (Ensiklopedia of Journal, 2025)
Administrative Law (HAN) plays a central role in guiding and controlling the exercise of administrative authority to ensure it remains within lawful and accountable boundaries. The General Principles of Good Governance (AUPB), such as legal certainty, transparency, accountability, and the prohibition of abuse of power, serve as key guidelines for establishing transparent and democratic governance. This article is structured using a library research approach to examine the implementation of AUPB in administrative practices in Indonesia and to identify the challenges faced. The findings indicate that the implementation of AUPB still encounters several obstacles, including limited understanding of its substantive principles among public officials, a bureaucratic culture resistant to openness, regulatory inconsistencies, and weak internal and external oversight mechanisms. Furthermore, the adaptation of AUPB in digital public service delivery requires institutional readiness and improved human resource capacity. Therefore, strengthening legal understanding, institutional reform, and the integration of AUPB principles into governance systems are necessary to realize clean, effective, and accountable public administration.Keywords: Administrative Law, AUPB, implementation, public governance, oversight